A randomized controlled study on intermittent theta pulse stimulation for improving cognitive impairment after stroke - Li, Fei; Hu, Fengxia; Liang, Yi; Liang, Fen; Tan, Huiqun; Xing, Sisi (Frontiers in Neurology, 2025)
ObjectiveThis study evaluates the efficacy and underlying mechanisms of intermittent theta-burst stimulation (iTBS) in improving cognitive function and quality of life in post-stroke patients.MethodsA total of 80 subacute stroke patients with cognitive deficits were randomly assigned to a control group (n = 40) receiving conventional treatment plus sham stimulation and an experimental group (n = 40) receiving conventional treatment plus iTBS over the left dorsolateral prefrontal cortex for 4 weeks.ResultsBaseline characteristics were comparable between groups. After 3 months, the experimental group demonstrated significantly greater improvements than the control group in scores for the Mini-Mental State Examination (MMSE; adjusted mean: 25.35 vs. 20.44, P < 0.001), Montreal Cognitive Assessment (MoCA; 26.49 vs. 24.57, P = 0.002), and Stroke-Specific Quality of Life (SS-QOL; 158.45 vs. 137.31, P < 0.001), and showed greater reduction in completion time for the Trail Making Test (TMT). Biochemically, the iTBS group exhibited significantly increased serum Brain-Derived Neurotrophic Factor (BDNF) and reduced levels of Tumor Necrosis Factor-alpha (TNF-α) and Interleukin-6 (IL-6) compared to the control group (all P < 0.001). Changes in BDNF levels correlated positively with improvements in MMSE scores (r = 0.58, P < 0.001).ConclusioniTBS is a safe and effective intervention that enhances cognitive recovery and quality of life in post-stroke patients. These benefits are associated with modulation of neuroplasticity and inflammatory markers, suggesting that iTBS may promote recovery by upregulating BDNF and attenuating neuroinflammation. Further research is needed to confirm these mechanisms.